Biomarkers in Cancer 2014
DOI: 10.1007/978-94-007-7744-6_29-1
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Circulating Biomarkers

Abstract: Circulating CRC markers might become useful tools for the massive screening of people since they satisfy a high degree of accuracy, noninvasiveness, reproducibility, and economy. Within circulating biomarkers, we will focus on the detection of autoantibodies in serum from cancer patients and their target tumorassociated antigens (TAAs). Although the sensitivity, specificity, and predictive value of individual TAAs present low scores, the combination of multiple TAAs shows improved values to discriminate betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…Previously, we and others have used different types and versions of high-density protein microarrays (phage microarrays, glycopeptide microarrays, natural protein microarrays and recombinant ORFs protein microarrays) to character-ize the CRC humoral response [11,[19][20][21][22][23] and several CRC TAAs have been described (for reviews see [24,25]). In addition, using CRC murine models we showed that autoantibody detection allows very early CRC diagnosis providing an effective demonstration that CRC TAAs can be used for cancer screening and preclinical diagnosis [11].…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Previously, we and others have used different types and versions of high-density protein microarrays (phage microarrays, glycopeptide microarrays, natural protein microarrays and recombinant ORFs protein microarrays) to character-ize the CRC humoral response [11,[19][20][21][22][23] and several CRC TAAs have been described (for reviews see [24,25]). In addition, using CRC murine models we showed that autoantibody detection allows very early CRC diagnosis providing an effective demonstration that CRC TAAs can be used for cancer screening and preclinical diagnosis [11].…”
Section: Significance Of the Studymentioning
confidence: 99%